Power quality measurement and analysis using higher-order statistics : understanding HOS contribution on the smart(er) grid /: understanding HOS contribution on the smart(er) grid. (2022) - Florencias-Oliveros, Olivia; González-de-la-Rosa, Juan-José Sierra-Fernández, José-María; Espinosa-Gavira, Manuel-Jesús; Agüera-Pérez, Agustín; Palomares-Salas, José-Carlos
No abstract available